THE RELEVANCE OF EDUCATING PRIMARY EDUCATION STUDENTS BASED ON NATIONAL CONTENT - Mirzaakbarov Abdurasul Mirzaakbarovich (The Conference Hub, 2025)
This article explores the relevance of educating students in the field of primary education using national content. The study employed methods such as literature analysis, surveys, and observations to evaluate the impact of national content on the educational process. The results demonstrated that national content enhances students’ interest in learning and their awareness of national identity; however, its effectiveness requires integration with modern pedagogical approaches. The article analyzes the advantages and limitations of this approach and provides practical recommendations. The research aims to contribute to the development of primary education and the preservation of national values.
Keywords: primary education, national content, student preparation, national values, pedagogical approach, educational effectiveness, cultural heritage, modern technologies.